2012
DOI: 10.1037/a0026062
|View full text |Cite
|
Sign up to set email alerts
|

Second-order relational face processing is applied to faces of different race and photographic contrast.

Abstract: A large body of research suggests that faces are processed by a specialized mechanism within the human visual system. This specialized mechanism is made up of subprocesses (Maurer, LeGrand, & Mondloch, 2002). One subprocess, called second- order relational processing, analyzes the metric distances between face parts. Importantly, it is well established that other-race faces and contrast-reversed faces are associated with impaired performance on numerous face processing tasks. Here, we investigated the specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Therefore, based on Loftus et al (2004) ’s model, our findings supported the existence of FIE, which was caused by stimuli categories (different Y for faces and non-faces) rather than varying degrees of configural and featural strength utilization. Besides, our results also suggested that there was no difference in the inversion effect between own- and other-race faces ( Buckhout and Regan, 1988 ; Rhodes et al, 2006 ; Matheson et al, 2012 ).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Therefore, based on Loftus et al (2004) ’s model, our findings supported the existence of FIE, which was caused by stimuli categories (different Y for faces and non-faces) rather than varying degrees of configural and featural strength utilization. Besides, our results also suggested that there was no difference in the inversion effect between own- and other-race faces ( Buckhout and Regan, 1988 ; Rhodes et al, 2006 ; Matheson et al, 2012 ).…”
Section: Discussionsupporting
confidence: 62%
“…As for inverted faces, several research found a larger FIE for own-than otherrace faces, implying the benefit of configural processing for own-race faces (Rhodes et al, 1989;Sangrigoli and de Schonen, 2004;Hancock and Rhodes, 2008;Megreya et al, 2011). Other studies, on the other hand, found that there was no difference in inversion decrement between own-and other-race faces (Buckhout and Regan, 1988;Rhodes et al, 2006;Matheson et al, 2012), or even that the inversion effect was larger for other-race faces than for own-race faces (Valentine and Bruce, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Despite little evidence regarding their validity, CG faces are being used to address important questions in face processing research. Examples include charting the developmental trajectory of face identity recognition [ 1 ], exploring the origins of race effects on face recognition [ 2 ], identifying the perceptual underpinnings of social judgements from faces such as trustworthiness [ 3 ], mapping the structure of face-space [ 4 ], investigating the types of faces for which there is special sensitivity to spacing between features in upright faces [ 5 ], and examining the category selectivity of neural responses to faces [ 6 ]. Results from such studies are being used to inform our understanding of how faces are processed and to develop and refine theories of face processing.…”
Section: Introductionmentioning
confidence: 99%